2020
DOI: 10.1111/cpr.12795
|View full text |Cite
|
Sign up to set email alerts
|

Exosome‐transferred long non‐coding RNA ASMTL‐AS1 contributes to malignant phenotypes in residual hepatocellular carcinoma after insufficient radiofrequency ablation

Abstract: Objectives Long non‐coding RNAs (lncRNAs) are emerging RNA regulators in cancer progression, including in hepatocellular carcinoma (HCC). Recently, insufficient radiofrequency ablation (RFA) has been reported to lead to recurrence and metastasis of residual HCC tumours. Herein, we aimed to the role of ASMTL‐AS1 in residual HCC after insufficient RFA. Materials and methods In vitro insufficient RFA model was simulated in Huh7 cells and subsequently named Huh7‐H cells. In vitro and in vivo assays were conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 43 publications
0
45
0
Order By: Relevance
“…Feng et al reported that ASMTL-AS1 was signi cantly downregulated in papillary thyroid carcinoma, which served as a tumor suppressor via inhibiting cell growth and glycolysis [13]. However, another study showed that ASMTL-AS1 was an oncogene in hepatocellular carcinoma that activated carcinogenic YAP signaling and promoted cancer recurrence or metastasis [14]. Herein, we found that ASMTL-AS1 was a tumor-inhibiting lncRNA in TNBC, inactivating oncogenic Wnt/β-catenin pathway and repressing cell proliferation and invasion, and restoration of ASMTL-AS1 expression signi cantly retarded the growth of tumor in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Feng et al reported that ASMTL-AS1 was signi cantly downregulated in papillary thyroid carcinoma, which served as a tumor suppressor via inhibiting cell growth and glycolysis [13]. However, another study showed that ASMTL-AS1 was an oncogene in hepatocellular carcinoma that activated carcinogenic YAP signaling and promoted cancer recurrence or metastasis [14]. Herein, we found that ASMTL-AS1 was a tumor-inhibiting lncRNA in TNBC, inactivating oncogenic Wnt/β-catenin pathway and repressing cell proliferation and invasion, and restoration of ASMTL-AS1 expression signi cantly retarded the growth of tumor in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive studies have shown that lncRNA serves as a ceRNA in various human diseases, such as the lnc-BCYRN1/miR-619-5p/CUEDC2 axis in glioma [10], lnc-DNM3OS/miR-126/IGF1 axis in osteoarthritis [11], and lnc-UCA1/miR-182-5p/DLL4 axis in renal cancer [12]. ASMTL-AS1 is a newly found lncRNA that locates at Xp22.33 and Yp11.2, which has been recently reported as a key player in papillary thyroid cancer [13] and hepatocellular carcinoma [14], and could be used as a prognostic biomarker for bladder cancer [15]. Nevertheless, its role in TNBC remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the research results on exosomal lncRNAs gradually increased. Using Huh7 cells in vitro to simulate the insufficient radiofrequency ablation (RFA), the researcher found that exosomal lncRNA ASMTL-AS1 activated miR-342-3p/NLK/YAP signals, aggravating residual malignant hepatocellular carcinoma when RFA was insufficient, opening up a new way for the treatment of HCC and preventing its recurrence 42 . Wang et al measured the expression of lncRNA H19 in HCC by qRT-PCR and western blot, and found that it could up-regulate LIMK1 and inhibit apoptosis, promote the proliferation, migration, and metastasis of HCC treated with propanol 43 .…”
Section: Biological Components Of Exosomesmentioning
confidence: 99%
“…For example, lncRNA H19 promotes proliferation and migration but inhibits apoptosis of HCC cells via sponging miR-520a-3p, thereby, upregulating the LIMK1 gene that encodes the LIM domain kinase 1 protein (111). Additionally, exosomal lncRNA ASMTL-AS1 can promote HCC malignancy via sponging miR-342-3p and transactivating c-Myc to promote oncogenic MAPK family Nemo-like kinase (NLK) expression and yes-associated protein 1 (YAP) activation (112).…”
Section: Genomic and Transcriptomic Profiling Of Exosomal Non-coding mentioning
confidence: 99%